A RETROSPECTIVE STUDY ON MULTI DRUG RESISTANT TUBERCULOSIS IN A TERTIARY CARE HOSPITAL: AN ALARMING THREAT OF CONCERN. - Seema, Kumari; Kumar, Abhay; Boipai, Manju; Ashok Kumar Sharma; Kumar, Manoj (Student’s Journal of Health Research Africa, 2023)
Introduction: MDR-TB is becoming a significant global health concern in this era. Globally, the incidence of MDR-TB is 3.4% in new cases and 18% in previously treated cases. MDR-TB mostly arises due to inadequate treatment, poor compliance to drugs, and/or direct contact with an MDR-TB patient and hence is essentially a man-made phenomenon. The prevalence of MDR-TB in any area is mirrored by the functional state and efficiency of tuberculosis control programs running in the country. Material and Method: A total of 549 cases were recruited during the period from 2017 to 2019 and the data were analysed retrospectively. Both pulmonary and extra-pulmonary samples were collected with proper aseptic measures. Direct microscopy by Ziehl Neelsen (ZN) staining was done. Further liquid culture and first-line drug susceptibility testing were performed in MGIT 960. Result: Out of 549 enrolled cases, 312 Mycobacterium tuberculosis cases were confirmed. The prevalence of mono or multi-drug resistance of MTB patients to 1st line drugs during 2017, 2018, and 2019 were 51.7%, 52.1%, and 49.1% respectively. The present study showed a prevalence of MDR-TB in new cases and of previously treated TB cases on an average of 2.7% and 11.2% which is slightly lower than the national level data of 3.4% and 18% respectively. Conclusion: India is showing an increased prevalence of MDR-TB which leads to the greatest obstacle to the End TB strategy adopted by WHO and the government of India. There is an urgent need for continuous surveillance of MDR-TB.